A multiplexable TALE-based binary expression system for in vivo cellular interaction studies. Issue 1 (December 2017) - Toegel, Markus; Azzam, Ghows; Lee, Eunice Y.; Knapp, David; Tan, Ying; Fa, Ming; Fulga, Tudor
Abstract Binary expression systems have revolutionised genetic research by enabling delivery of loss-of-function and gain-of-function transgenes with precise spatial-temporal resolution in vivo. However, at present, each existing platform relies on a defined exogenous transcription activator capable of binding a unique recognition sequence. Consequently, none of these technologies alone can be used to simultaneously target different tissues or cell types in the same organism. Here, we report a modular system based on programmable transcription activator-like effector (TALE) proteins, which enables parallel expression of multiple transgenes in spatially distinct tissues in vivo. Using endogenous enhancers coupled to TALE drivers, we demonstrate multiplexed orthogonal activation of several transgenes carrying cognate variable activating sequences (VAS) in distinct neighbouring cell types of theDrosophila central nervous system. Since the number of combinatorial TALE–VAS pairs is virtually unlimited, this platform provides an experimental framework for highly complex genetic manipulation studies in vivo. Binary expression systems enable researchers to deliver loss-of-function or gain-of-function transgenes with spatial-temporal resolution in vivo. Here, the authors present a programmable TALE-based system for multiplexed orthogonal activation of transgenes inDrosophila .